Smart Poly(lactide)-b-poly(triethylene glycol methyl ether methacrylate) (PLA-b-PTEGMA) Block Copolymers: One-Pot Synthesis, Temperature Behavior, and Controlled Release of Paclitaxel - Svetlana Lukáš Petrova; Martina Vragović; Ewa Pavlova; Zulfiya Černochová; Alessandro Jäger; Eliézer Jäger; Rafał Konefał (MDPI AG, 2023)
This paper introduces a new class of amphiphilic block copolymers created by combining two polymers: polylactic acid (PLA), a biocompatible and biodegradable hydrophobic polyester used for cargo encapsulation, and a hydrophilic polymer composed of oligo ethylene glycol chains (triethylene glycol methyl ether methacrylate, TEGMA), which provides stability and repellent properties with added thermo-responsiveness. The PLA-b-PTEGMA block copolymers were synthesized using ring-opening polymerization (ROP) and reversible addition-fragmentation chain transfer (RAFT) polymerization (ROP-RAFT), resulting in varying ratios between the hydrophobic and hydrophilic blocks. Standard techniques, such as size exclusion chromatography (SEC) and 1H NMR spectroscopy, were used to characterize the block copolymers, while 1H NMR spectroscopy, 2D nuclear Overhauser effect spectroscopy (NOESY), and dynamic light scattering (DLS) were used to analyze the effect of the hydrophobic PLA block on the LCST of the PTEGMA block in aqueous solutions. The results show that the LCST values for the block copolymers decreased with increasing PLA content in the copolymer. The selected block copolymer presented LCST transitions at physiologically relevant temperatures, making it suitable for manufacturing nanoparticles (NPs) and drug encapsulation-release of the chemotherapeutic paclitaxel (PTX) via temperature-triggered drug release mechanism. The drug release profile was found to be temperature-dependent, with PTX release being sustained at all tested conditions, but substantially accelerated at 37 and 40 °C compared to 25 °C. The NPs were stable under simulated physiological conditions. These findings demonstrate that the addition of hydrophobic monomers, such as PLA, can tune the LCST temperatures of thermo-responsive polymers, and that PLA-b-PTEGMA copolymers have great potential for use in drug and gene delivery systems via temperature-triggered drug release mechanisms in biomedicine applications.